2019
DOI: 10.33249/2663-2144-2019-78-5-58-67
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of wheat bread technology enriched with nonconventional plant ingredients

Abstract: Уманський національний університет садівництва Інститутська, 1, м. Умань, 20300, Україна Удосконалено технологію збагачення хліба з борошна пшеничного вищого сорту добавкою натурального походження (порошками із плодів хеномелесу). Проаналізовано і вивчено фактори, які зумовлюють необхідність підвищення харчової цінності хлібобулочних виробів; проаналізовані перспективи розвитку функціонального харчування; проведено огляд натуральних добавок з метою їх використання у виробництві хлібобулочних виробів; проана… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…At the same time, changes in the surface of bread and the color of the crumb are due to the presence of coloring substances in the paste. This has been proven in studies [27], where the addition of fruit and vegetable raw materials changed the sensory performance of bread due to coloring substances. Other studies [28] have found that the sweet taste of bread crumb is due to the presence of pumpkin sugar in the paste.…”
Section: Discussion Of Results Of the Study Of Expanding The Range Of...mentioning
confidence: 86%
“…At the same time, changes in the surface of bread and the color of the crumb are due to the presence of coloring substances in the paste. This has been proven in studies [27], where the addition of fruit and vegetable raw materials changed the sensory performance of bread due to coloring substances. Other studies [28] have found that the sweet taste of bread crumb is due to the presence of pumpkin sugar in the paste.…”
Section: Discussion Of Results Of the Study Of Expanding The Range Of...mentioning
confidence: 86%
“…Pumpkin flour is a promising raw material for enriching flour products with valuable nutrients [3]. It is known [4] that pumpkin flour contains 6.1 % water, 8.2 % protein, 0.7 % fat, 2.3 % ash, 27.4 % dietary fiber, which includes soluble (10.2 %) and insoluble (17.2 %) fiber.…”
Section: Introductionmentioning
confidence: 99%
“…During consumption, the smell and taste of milk thistle is felt. Promising is the use of flour from hawthorn fruit [5], powder of dried apples, raspberries, calendula leaves, pumpkin oil [6].…”
Section: Introductionmentioning
confidence: 99%